2021
DOI: 10.1038/s41586-021-03370-0
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and biophysical determinants of grass leaf size worldwide

Abstract: One of the most striking ecological trends is the association of small leaves with dry and cold climates, described 2400 years ago by Theophrastus, and recently recognized for eudicotyledonous plants at the global scale 1-3 . For eudicotyledons, this pattern is attributed 24 to small leaves having a thinner boundary layer to avoid extreme leaf temperatures 4 , and 25 their developing vein traits that improve water transport under cold or dry climates 5,6 . Yet, 26 the global distribution of leaf size and its m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 152 publications
5
74
0
1
Order By: Relevance
“…Plants have acquired a suite of traits that allow them to adapt to the environmental conditions of their habitats (Baird et al, 2021; Brodribb, Powers, Cochard, & Choat, 2020; Choat et al, 2012; Fu & Meinzer, 2018; Meinzer et al, 2016, 2017; Yao, Nie, et al, 2021). Among them, hydraulic traits related to efficient water transport and resistance to hydraulic dysfunction are of particular importance (Brodribb, Powers, Cochard, & Choat, 2020; Li et al, 2020; Liu et al, 2018; Scoffoni, Sack, & Ort, 2017), and efficient water transport could trade‐off against protecting hydraulic systems from loss of function (Nardini, Pedà, & Rocca, 2012; Scoffoni, Sack, & Ort, 2017) to allow species to adapt to habitats with different precipitation levels (Choat et al, 2012; Ocheltree, Nippert, & Prasad, 2016; Scoffoni, Sack, & Ort, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have acquired a suite of traits that allow them to adapt to the environmental conditions of their habitats (Baird et al, 2021; Brodribb, Powers, Cochard, & Choat, 2020; Choat et al, 2012; Fu & Meinzer, 2018; Meinzer et al, 2016, 2017; Yao, Nie, et al, 2021). Among them, hydraulic traits related to efficient water transport and resistance to hydraulic dysfunction are of particular importance (Brodribb, Powers, Cochard, & Choat, 2020; Li et al, 2020; Liu et al, 2018; Scoffoni, Sack, & Ort, 2017), and efficient water transport could trade‐off against protecting hydraulic systems from loss of function (Nardini, Pedà, & Rocca, 2012; Scoffoni, Sack, & Ort, 2017) to allow species to adapt to habitats with different precipitation levels (Choat et al, 2012; Ocheltree, Nippert, & Prasad, 2016; Scoffoni, Sack, & Ort, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…VLA and VLA minor showed no varietal differences in the present study, which was perhaps due to the few genotypes used, and their vein traits ranged very narrowly. Rice leaf veins are distributed in parallel, and the leaf vein density is strongly affected by the leaf width (Baird et al, 2021 ). For example, Tabassum et al ( 2016 ) reported that polyethylene glycol–induced water deficit caused rice leaf narrowing and led to an increase in leaf density.…”
Section: Discussionmentioning
confidence: 99%
“…Simonin et al ( 2012 ) demonstrated that K leaf increased with leaf area. However, a recent study exploring the development and biophysical determinations of grass leaf size worldwide revealed that small leaves have hydraulic benefits due to their higher VLA major (Baird et al, 2021 ). Optimal leaf morphological and anatomical traits for improving K leaf and P N should be defined to provide theories for high photosynthetic capacity rice breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Short growing seasons may promote a quick return-on-investment strategy of low tissue construction costs and high photosynthetic capacity (Baird et al 2021). In the southern habitat typical of the lowland ecotype, the long growing season may select for longer-lived leaves with higher LMA.…”
Section: Discussionmentioning
confidence: 99%